PENGENDALIAN NON PERFOMING LOAN LAPORAN LABA RUGI BANK RAKYAT INDONESIA UNIT CEMPAKA PUTIH PADA SEKTOR KREDIT BISNIS MIKRO PERIODE JANUARI – DESEMBER 2014 - Krisna Hidajat; Yanuar Adi Putra; Maryadi Maryadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
This study emphasizes the control of Non-Performing Loans, especially in micro-business lending carried out by Bank Rakyat Indonesia Cempaka Putih Unit. From the results of direct observation it was found that there was fictitious credit distribution, did not meet credit procedure standards and NPL control systems that have not been implemented properly.